2010
DOI: 10.1167/iovs.10-5251
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Structure and Function of Als2cr4 in the Mouse Retina

Abstract: Als2cr4 is a novel protein, with a probable tetraspanin-like membrane structure, that is localized in photoreceptors and in the postsynaptic outer plexiform layer and that interacts with cytoskeletal proteins. Als2cr4 may be involved in membrane transport between the photoreceptor inner and outer segments and may be a key component in maintaining the structural integrity of the outer segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
(40 reference statements)
1
13
1
Order By: Relevance
“…, 2010 ) at 1.5 μg/ml, rabbit anti-Ofd1 ( Singla et al. , 2010 ) at 1:1000, rabbit anti-Sdccag8 (13471-1-AP; Proteintech, Chicago, IL) at 1:500, rabbit anti-Smoothened (ab38686; Abcam) at 1:1000, and rabbit anti-Tmem237 ( Zuniga and Craft, 2010 ) at 1:500. For Western blots, the following antibodies were used: mouse anti–α-tubulin (DM1α; Sigma-Aldrich) at 1:10,000 and rabbit anti-Ahi1 (22045-1-AP; Proteintech) at 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…, 2010 ) at 1.5 μg/ml, rabbit anti-Ofd1 ( Singla et al. , 2010 ) at 1:1000, rabbit anti-Sdccag8 (13471-1-AP; Proteintech, Chicago, IL) at 1:500, rabbit anti-Smoothened (ab38686; Abcam) at 1:1000, and rabbit anti-Tmem237 ( Zuniga and Craft, 2010 ) at 1:500. For Western blots, the following antibodies were used: mouse anti–α-tubulin (DM1α; Sigma-Aldrich) at 1:10,000 and rabbit anti-Ahi1 (22045-1-AP; Proteintech) at 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…The cytoskeleton has been implicated in many aspects of vision ranging from structural maintenance of photoreceptors to protein trafficking between the inner segment and outer segment and for active transport in the connecting cilium [40]. Narimatsu et al [41] demonstrated that light exposure to the mice caused disruption of the actin cytoskeleton of RPE via oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…TMEM237 is part of the ciliary transition zone complex and mutations underlie cases of Joubert syndrome related disorders, which are ciliopathies with associated vision defects. 63,64 Aside from a proposed role controlling protein movement in and out of the outer segment as part of the ciliary gate, TMEM237 is also expressed in rod outer segments 64 and therefore may influence photoreceptor morphology in multiple ways.…”
Section: Müller Glia and Rpementioning
confidence: 99%